2017
DOI: 10.1007/s00520-016-3543-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypercalcaemia and hypocalcaemia: finding the balance

Abstract: Calcium metabolism in cancer and hypercalcaemia of malignancyThe balance between bone formation and resorption may be disrupted in patients with cancer, leading either to increased bone resorption, calcium release, and possibly hypercalcaemia, or to increased bone formation, sequestration of calcium, and possibly hypocalcaemia. In adults, hypercalcaemia of malignancy is most common in patients with tumours that produce factors that induce osteoclast activation and enhance bone resorption. Impaired renal functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 78 publications
1
21
0
2
Order By: Relevance
“…In this study, denosumab was found to lower serum calcium levels in 21 of 33 (64%) patients within 10 days [ 77 ]. Due to an increased risk of hypocalcemia with denosumab, patients should be monitored post-treatment as they may require calcium and vitamin D supplementation [ 78 ]. Results from larger studies with longer-term evaluation after denosumab treatment are needed.…”
Section: Management Of Potentially Reversible Precipitantsmentioning
confidence: 99%
“…In this study, denosumab was found to lower serum calcium levels in 21 of 33 (64%) patients within 10 days [ 77 ]. Due to an increased risk of hypocalcemia with denosumab, patients should be monitored post-treatment as they may require calcium and vitamin D supplementation [ 78 ]. Results from larger studies with longer-term evaluation after denosumab treatment are needed.…”
Section: Management Of Potentially Reversible Precipitantsmentioning
confidence: 99%
“…In the presence of metabolic imbalances produced by the cross-sex pharmacologic therapies, the blood calcium balance system can be altered, thereby playing an important role as an ethiological factor for pharmacologically induced osteoporosis [48].…”
Section: Discussionmentioning
confidence: 99%
“…Hypercalcemia can develop when the predominant force is osteoclastic, and hypocalcemia can develop due to calcium sequestration when the driving force is osteoblastic. Although cancers can exhibit predominantly increased resorption or formation of bone, a mixed picture is not uncommonly observed (33,34,35). Increased resorption and impaired formation are driven by local factors and humoral tumor factors produced by the tumor.…”
Section: Osteolyticmentioning
confidence: 99%